THE SYNTHESIS OF GLYCEROL CARBONATE FROM BIODIESEL BY PRODUCT GLYCEROL AND UREA OVER AMBERLYST 15 - Suyatmo, Reviana Inda Dwi; Sulistyo, Hary; Sediawan, Wahyudi Budi (Universitas Negeri Semarang, 2017)
The growing utilization of biodiesel as a renewable fuel has generated a large surplus of glycerol as a major byproduct. The prices of glycerol continue to drop in such an oversaturated market. Therefore, new uses are being developed for glycerol to produce value-added chemicals. Among those chemicals, glycerol carbonate has many application in various fields. Glycerol carbonate is mostly used as a solvent in cosmetic and pharmacheutical industries due to its low toxicity, high boiling point, and low vapor pressure. The synthesis of glycerol carbonate from glycerol and urea using Amberlyst15 as a catalyst was being conducted in this study. The reaction was carried out using a batch reactor for 5 hours with the condition of the reaction temperature was around 120oC, mole ratios of reactant of urea:glycerol were 0.8:1, 0.9:1, 1:1, and 1.2:1 , catalyst concentrations were 2%, 2,5%, 3%, and 4%, and mixing speeds were 370 rpm, 525 rpm, and 700 rpm.Â It is found that the optimum conversion of glycerol was obtained at 120oC with 5 hours of reaction using an equimolar amount of glycerol and urea with catalyst load of 3%. Mixing speed did not affect glycerol conversion. Amberlyst15 as catalyst was also stable enough to be reused at least for three times.